Vanishing and Returning Heroes: Ambiguity and Persistent Hope in an Unea Island Legend - Blythe, Jennifer (Anthropologica, 2022)
Throughout Melanesia, there are stories of creative heroes who leave their people. The tale of Mataluangi is told in Unea, an island in West New Britain, Papua New Guinea. The legend of the snake hero is related to its ethnographic context and the story is analyzed to show its conformity to a type of origin myth, vuvumu, that is prevalent in Unea. It is suggested that the structure of this well-known legend and other vuvumu stories influence contemporary politics in Unea as well as how Islanders perceive their history and possible future.